Exposures to Elevated Core Temperatures during Football Training: The Impact on Autonomic Nervous System Recovery and Function - Eric Renaghan; Harrison L. Wittels; Luis A. Feigenbaum; Michael J. Wishon; Stephanie Chong; Eva D. Wittels; Stephanie Hendricks; Dustin Hecocks; Kyle Bellamy; Joe Girardi; Stephen Lee; Tri Vo; et al. (MDPI AG, 2023)
Exercising with elevated core temperatures may negatively affect autonomic nervous system (ANS) function. Additionally, longer training duration under higher core temperatures may augment these negative effects. This study evaluated the relationship between exercise training duration and 24 h ANS recovery and function at ≥37 °C, ≥38 °C and ≥39 °C core temperature thresholds in a sample of male Division I (D1) collegiate American football athletes. Fifty athletes were followed over their 25-week season. Using armband monitors (Warfighter MonitorTM, Tiger Tech Solutions, Inc., Miami, FL, USA), core temperature (°C) and 24 h post-exercise baseline heart rate (HR), HR recovery and heart rate variability (HRV) were measured. For HRV, two time-domain indices were measured: the root mean square of the standard deviation of the NN interval (rMSSD) and the standard deviation of the NN interval (SDNN). Linear regression models were performed to evaluate the associations between exercise training duration and ANS recovery (baseline HR and HRV) and function (HR recovery) at ≥37 °C, ≥38 °C and ≥39 °C core temperature thresholds. On average, the athletes were 21.3 (± 1.4) years old, weighed 103.0 (±20.2) kg and had a body fat percentage of 15.4% (±7.8%, 3.0% to 36.0%). The duration of training sessions was, on average, 161.1 (±40.6) min and they ranged from 90.1 to 339.6 min. Statistically significant associations between training duration and 24 h ANS recovery and function were observed at both the ≥38.0 °C (baseline HR: β = 0.10 ± 0.02, R2 = 0.26, p < 0.0000; HR recovery: β = −0.06 ± 0.02, R2 = 0.21, p = 0.0002; rMSSD: β = −0.11 ± 0.02, R2 = 0.24, p < 0.0000; and SDNN: β = −0.16 ± 0.04, R2 = 0.22, p < 0.0000) and ≥39.0 °C thresholds (β = 0.39 ± 0.05, R2 = 0.62, p < 0.0000; HR recovery: β = −0.26 ± 0.04, R2 = 0.52, p < 0.0000; rMSSD: β = −0.37 ± 0.05, R2 = 0.58, p < 0.0000; and SDNN: β = −0.67 ± 0.09, R2 = 0.59, p < 0.0000). With increasing core temperatures, increases in slope steepness and strengths of the associations were observed, indicating accelerated ANS deterioration. These findings demonstrate that exercise training under elevated core temperatures (≥38 °C) may negatively influence ANS recovery and function 24 h post exercise and progressively worsen.